Sinus arrhythmia in children with atrial septal defect: an analysis of heart rate variability before and after surgical repair. Issue 3 (March 1989) - Finley, J P; Nugent, S T; Hellenbrand, W; Craig, M; Gillis, D A
Abstract : The expression of sinus arrhythmia depends on separation of the systemic and pulmonary venous return to the heart as well as on normal autonomic control mechanisms. Patients with atrial septal defect provide a naturally occurring experiment of communication between the two venous systems. In adults with atrial septal defect sinus arrhythmia is minimal or absent. But children with atrial septal defect retain appreciable sinus arrhythmia, although this is not recognised in published reports. To understand why this is so, continuous electrocardiograms were recorded before and after operation in 10 children (aged 4-16 years, mean 6.3) with atrial septal defects and in 10 normal children (aged 5-7 years, mean 6.1). Mean RR intervals were calculated for periods of one minute, and the standard deviation was used as an index of heart rate variability (that is sinus arrhythmia). Frequency analysis (spectral analysis) was also performed on a continuous beat to beat record of heart rate to describe the frequency components that may reflect autonomic activity. The results confirmed the presence of considerable sinus arrhythmia in children with unoperated atrial septal defect. None the less, the standard deviation of RR intervals in the children with unoperated atrial septal defect was significantly less than that for the normal children, and variation increased after closure of the defect. Power spectral analysis of instantaneous heart rate indicated that the high frequency (0.15-0.45 Hz) vagally mediated component of variability was lower for patients than for controls which may indicate abnormalities of autonomic control of heart rate in these children. The comparative retention of sinus arrhythmia in children with atrial septal defect may relate to the small size of the right atrium or differences in myocardial compliance compared with adults.